Effectiveness Of Waste Management At The Hamlet Level In Mamasa Village Mamasa Regency - Mildayati - (Hasanuddin University, 2021)
Population growth and changes in people's consumption patterns lead to an increase in the volume, types and characteristics of increasingly diverse waste. This increase in the amount of waste that is not followed by the repairment and improvement of waste management facilities and infrastructure has resulted in a complex waste problem. Therefore, one of the efforts that can be applied to overcome the waste problem is by taking a source approach. In this approach, waste will be handled (managed) at the upstream (source) before it reaches the landfill (downstream). Ways that can be done include sorting the waste and also the 3R (reduce, reuse and recycle) program. This study aims to determine the effectiveness of waste management at the hamlet level in Mamasa Village, Mamasa Regency. This study uses a descriptive qualitative approach with data reduction analysis. The results showed that the effectiveness of waste management was 37.5% and the effectiveness of waste reduction was 42%. The study concluded that the effectiveness of waste management at the hamlet level in Mamasa village was not very effective.